Characterization of Cry toxins from autochthonous Bacillus thuringiensis isolates from Mexico - Raquel Camacho-Millán; Elsa Maribel Aguilar-Medina; Héctor Quezada; Óscar Medina-Contreras; Genaro Patiño-López; Héctor Manuel Cárdenas-Cota; Rosalío Ramos-Payán (Permanyer, 2017)
Background: Chemical pesticides, widely used in agriculture and vector-borne disease control, have shown toxic effects on the environment and the people in contact with them. Bacillus thuringiensis is a widely used bacterium for alternative and safer control of insect pests. Its toxins are specific for insects but innocuous for mammals and may be used as powerful adjuvants when applied with vaccines. The objective of this work was to characterize some autochthonous B. thuringiensis strains, which could be used for the control of a local pest (Diatraea considerata Heinrich) that affects sugar cane crops in Sinaloa, Mexico. Also, to evaluate these strains as a source of Cry toxins, which may be used in the future as adjuvants for some vaccines. Methods: Eight strains from field-collected dead insects were isolated. These were microbiologically identified as B. thuringiensis and confirmed by amplification and sequencing of 16S rDNA. Bioassays were performed to evaluate their pathogenicity against D. considerata, and Cry toxins were identified by proteomic analyses. Results: An increased mortality among larvae infected with strain Bt-D was observed, and its toxin was identified as Cry1Ac. Conclusions: The observed data showed that the selected strain was pathogenic to D. considerata and seemed to produce Cry1Ac protein, which has been reported as an adjuvant in different types of immunization.